Randomised controlled trial evaluating the impact of different methods of HPV DNA testing for cervical cancer screening in Singapore’s primary care settings: a study protocol - Joanne Ngeow; Michelle Jessica Pereira; Xin Rong Ng; Sabrina Kay Wye Wong; Imm Pin Quek; Joseph Antonio Molina (BMJ Open)
Introduction Cervical cancer remains a significant public health concern in Singapore, with current screening rates at 43%, well below the national target of 70%. In 2019, human papillomavirus (HPV) DNA testing was introduced into the national cervical cancer screening programme, but barriers to participation include embarrassment, privacy concerns and discomfort with clinician-sampled tests. Self-sampled HPV DNA testing offers a promising alternative by providing more privacy and convenience. This study aims to evaluate the impact of including self-sampled HPV DNA testing as an alternative to clinician-sampling on screening uptake, clinical outcomes and cost-effectiveness in primary care.Methods and analysis This pragmatic, open-label, two-arm randomised controlled trial employs a Zelen design. A total of 650 women aged 30–69 who are due for cervical cancer screening will be recruited from National Healthcare Group Polyclinics in Singapore. Participants will be randomly assigned to either the intervention arm (offering both self-sampling and clinician-sampling) or the usual care arm (clinician-sampling only). The primary outcome is the proportion of participants in each arm detected with high-risk HPV. Secondary outcomes include the proportion of participants in each arm who undergo cervical cancer screening (uptake), are referred for colposcopy and are detected with CIN 2/3 or cervical cancer, as well as cost-effectiveness. Acceptability and feasibility of self-sampling will be evaluated through post-screening questionnaires.Ethics and dissemination Ethical approval was granted by the National Healthcare Group Domain Specific Review Board. Study results will be disseminated through peer-reviewed journals, healthcare conferences and shared with policymakers to guide potential inclusion of self-sampling in Singapore’s national cervical cancer screening programme. Findings from this trial will provide crucial evidence for the potential inclusion of self-sampling in Singapore’s national cervical cancer screening programme, which could increase screening rates and improve public health outcomes.Trial registration number ClinicalTrials.gov: NCT06528184.